Hyperparathyroidism due to eutopic PTH secretion from an ectopic intrathymic parathyroid cyst - Hoi W.H. (Japanese Editorial Committee of Annals of Thoracic and Cardiovascular Surgery, 2020)
10.5761/atcs.cr.10.01634